Factors Associated With Undernutrition In Children in Tanjung Raya Village, Teluk Dalam District Simeulue District - Us , Hafsah; Sembiring , Julina Br; Safitri, Mey Elisa (Institute Of Computer Science (IOCS), 2024)
Based on data from the World Health Organization (WHO) in 2018, 49% of the 10.4 million deaths of children under five in developing countries were related to malnutrition. It is recorded that around 50% of children under five in Asia suffer from malnutrition (UNICEf, 2018). Nationally, the prevalence of malnutrition and malnutrition is still fluctuating. Objective: To determine the factors associated with poor nutrition in toddlers in Tanjung Raya Village, Teluk Dalam District, Simeulue Regency in 2023. Method: The research design used an analytical survey with a cross sectional approach. The population used was all mothers who had toddlers in Tanjung Raya Village, Teluk Dalam District, Simeulue Regency. The sampling technique used total sampling, namely 43 respondents. The data instrument used was a questionnaire that was distributed and filled in directly by respondents. Data analysis used the chi-square test with significance ?=0.05. Results: The chi-square test shows that there is a relationship between maternal knowledge and malnutrition with p-value = 0.002, there is a relationship between maternal attitudes and malnutrition with p-value = 0.009, there is a parenting pattern with undernutrition with p-value = 0.005. Conclusion: There is a relationship between maternal knowledge, attitudes and parenting patterns and malnutrition among toddlers in Tanjung Raya Village, Teluk Dalam District, Simeulue Regency in 2023. The results of this research are expected to be a reference for improving knowledge, attitudes and parenting patterns of mothers with malnutrition in toddlers